Media Interaktif sebagai Literasi Digital Era 21 untuk Pembelajaran Sekolah Dasar - Ersha Amalia Listyawan; Iin Karlina; Vania Ayushandra (Proseding Didaktis: Seminar Nasional Pendidikan Dasar, 2021)
With technology from age to age increasingly sophisticated in the needs of all of us. Technological progress is accelerating, and with digital literacy through interpainful media it is easier for students to achieve excellence and educational goals. Education in the 21st era, students are more likely to close or adapt to learning through the media because it portrays material through digital literacy with interactive media to achieve the purpose of learning. The methods used in this study use the analysis of content from various journals by describing them. With this study, researchers have excavated digital literations regarding interactive media for elementary school children. The study also brought positive values with informative, inspiring and useful value. As a result of this study, it presents interactive media as text, animation, or comics, existing media from youtube, powerpoint given by teachers or getting information from the Internet, kahoot, edmodo, Google classroom, Google meet, quiziz, e-book or something else and can be used as a digital literacy for students or readers to understand.